KEBIJAKAN RUSIA MENGELUARKAN HAK VETO TERHADAP RANCANGAN RESOLUSI DEWAN KEAMANAN PBB TENTANG KONFLIK SIPIL DI SURIAH - Putri, Sabrina Nurastuti Sudirman; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This paper describes Russia’s decision in issuing veto against the UN Security Council resolution drafts on Syria civil conflict in 2011 to 2012. The conflict in Syria is a civil conflict that demands the Syrian president to step down. In the face of the civil conflict, the Syrian government often used military and armed forces that resulted in the loss of life of many civilians. Seeing the Syrian government action taken in the face of this conflict, the UN Security Council drafted resolutions on Syria to help resolve the internal conflicts. The first draft of the UN Security Council resolution was made in 2011and was vetoed by Russia and China. The second UN Security Council resolution was drafted back in 2012, and Russia and China once again vetoed it. The theory applied in this research is foreign policy and the rational actor model with nation-state as the level of analysis. Foreign policy, based on the rational actor model is considered as a result of the actions of rational actors. Analysis of the nation-state level to examine how a decision can be made to produce a policy. Sources of data used in this study is from books, journals, newspapers and the Internet. The study founds that the two vetos by Russia at the sessions of the UN Security Council were taken because Russia has a political and security interests in Syria. Russia does not want to lose its influence and hegemony in Syria.Keywords: foreign policy, the Security Council resolution, civil conflict, veto